2012
DOI: 10.1111/j.1600-6143.2011.03927.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Race and Poverty on Steps to Kidney Transplantation in the Southeastern United States

Abstract: Racial disparities in access to renal transplantation exist, but the effects of race and socioeconomic status (SES) on early steps of renal transplantation have not been well explored. Adult patients referred for renal transplant evaluation at a single transplant center in the Southeastern United States from 2005 to 2007, followed through May 2010, were examined. Demographic and clinical data were obtained from patient's medical records and then linked with United States Renal Data System and American Communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
156
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(162 citation statements)
references
References 32 publications
6
156
0
Order By: Relevance
“…However, one promising strategy for improving transplant education in centers with low-SES patients and those in rural areas farther away from transplant centers may be to provide educators with training about transplant's value for their patients; access to more patient-centered educational resources about transplantation; and resources, such as free transportation to a transplant center or more reimbursement for evaluation-related expenses to overcome patients' financial burdens related to transplant (9,27,28). Consistent with prior studies (10,(29)(30)(31), we also found that patients in centers with greater proportions of black patients had significantly lower transplant wait-listing rates. It is known that patients identifying as racial minorities are less likely to receive transplant education (7,32); however, we found a significant race effect on wait-listing rates even when controlling for the number of educational practices occurring within the center.…”
Section: Discussionmentioning
confidence: 55%
“…However, one promising strategy for improving transplant education in centers with low-SES patients and those in rural areas farther away from transplant centers may be to provide educators with training about transplant's value for their patients; access to more patient-centered educational resources about transplantation; and resources, such as free transportation to a transplant center or more reimbursement for evaluation-related expenses to overcome patients' financial burdens related to transplant (9,27,28). Consistent with prior studies (10,(29)(30)(31), we also found that patients in centers with greater proportions of black patients had significantly lower transplant wait-listing rates. It is known that patients identifying as racial minorities are less likely to receive transplant education (7,32); however, we found a significant race effect on wait-listing rates even when controlling for the number of educational practices occurring within the center.…”
Section: Discussionmentioning
confidence: 55%
“…Although racial disparities in transplant have been firmly established (3,5), few studies have compared the effect of large sets of less-and more-modifiable patient characteristics to determine where best to intervene to increase patients' successful completion of evaluation and receipt of LDKTs (11). From the beginning of the transplantseeking process, our study found that blacks began transplant evaluation less willing to get on the deceased donor waitlist, less willing for LDKT, and less knowledgeable about the benefits of transplant compared with whites.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the higher prevalence of CKD among blacks (1,2), they are less likely than whites to receive deceased donor transplants (DDKTs) and living donor transplants (LDKTs) (3,4), even after adjusting for clinical and sociodemographic characteristics (5). In 2009, blacks received just 14% of LDKTs, despite being 28% of ESRD incident patients in that year (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Despite strong evidence for improved quality of life and survival after transplantation, there is a large gap between the number of patients who need a kidney transplant and the number of available organs (2). Racial disparities in access to kidney transplantation have been documented in several steps in the renal transplant process, including referral, evaluation completion, and waitlisting (3)(4)(5)(6)(7)(8)(9). The reasons for the disparities are likely multifactorial, and they may not be entirely explained by clinical factors (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%